ASSESSING READING TEXT IN ENGLISH TEXTBOOK FOR ELEVENTH GRADER PUBLISHED BY MINISTRY OF EDUCATION AND CULTURE - Rohib Adrianto Sangia (Universitas Negeri Surabaya, 2017)
This research aims to answer the problems concerning the reading text material in English Textbook for Eleventh Grader published by Ministry of Education and Culture based on theory of good reading text (Nuttall, 2005). From three criteria proposed, this research focuses on the readability and suitability of reading text. There are two quantitative methods used in assessing readability, they are Miyazaki EFL Readability Formula and McAlpine® EFLAW Formula. In terms of assessing text suitability, the qualitative method is used by checking the target language covered by the reading text as the indicator of text suitability. Based on text readability, it is found out that overall reading texts Miyazaki EFL Readability score is 54.38 that can be interpreted as the reading text is in the level of fairly difficult and suitable to eleventh grader. While using McAlpine® EFLAW Formula, the readability score achieves 18.89, meaning that the reading text in English textbook of eleventh grader is easy to understand. In terms of suitability, it shows that, from 22 items of target language that is expected to be covered by the text, there are only 12 items which contain the target language which means text suitability is about 54.54% from overall text.